Quasispecies tropism and compartmentalization in gut and peripheral blood during early and chronic phases of HIV‐1 infection: possible correlation with immune activation markers. (18th October 2013) - Rozera, G.; Abbate, I.; Vlassi, C.; Giombini, E.; Lionetti, R.; Selleri, M.; Zaccaro, P.; Bartolini, B.; Corpolongo, A.; D'Offizi, G.; Baiocchini, A.; Del Nonno, F.; et al.
Abstract HIV quasispecies was analysed in plasma and proviral genomes hosted by duodenal mucosa and peripheral blood cells (PBMC) from patients with early or chronic infection, with respect to viral heterogeneity, tropism compartmentalization and extent of immune activation. Seventeen HIV‐1‐infected combined antiretroviral therapy naive patients were enrolled (11 early infection and six chronic infection). V3 and nef genomic regions were analysed by ultra‐deep pyrosequencing. Sequences were used to infer co‐receptor usage and to construct phylogenetic trees. As markers of immune activation, plasma sCD14 and soluble tumour necrosis factor receptor II (sTNFRII) levels were measured. Median diversity of HIV RNA was lower in patients with early infection versus chronic infection patients. Overall, direct correlation was observed between V3 diversity and X4 frequency; V3 diversity of HIV RNA was inversely correlated with CD4 T‐cell count; median sCD14 and sTNFRII values were similar in early and chronic patients, but X4 frequency of HIV RNA was directly correlated with plasma sCD14. The proportion of patients harbouring X4 variants and median intra‐patient X4 frequency of proviral genomes tended to be higher in chronic infection than early infection patients. More pronounced compartmentalization of proviral quasispecies in gut compared with PBMC samples was observed in patients with early infection compared with chronic patients. The loss of gut/PBMC compartmentalization in more advanced stages of HIV infection was confirmed by longitudinal observation. More studies are needed to understand the pathogenetic significance of early HIV quasispecies compartmentalization and progressive intermixing of viral variants in subsequent phases of the infection, as well as the role of immune activation in tropism switch.